2017
DOI: 10.1016/j.ydbio.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal stem cell ablation reveals differential requirements for survival in response to chemical challenge

Abstract: The Drosophila intestine is maintained by multipotent intestinal stem cells (ISCs). Although increased intestinal stem cell (ISC) proliferation has been correlated with a decrease in longevity, there is some discrepancy regarding whether a decrease or block in proliferation also has negative consequences. Here we identify headcase (hdc) as a novel marker of ISCs and enteroblasts (EBs) and demonstrate that Hdc function is required to prevent ISC/EB loss through apoptosis. Hdc depletion was used as a strategy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
5
10
1
Order By: Relevance
“…S3, D–F). We previously reported that flies lacking ISCs did not demonstrate decreased survival under control conditions; however, these flies had decreased rates of survival in response to bleomycin exposure ( Resende et al, 2017 ). Collectively, these data indicate that limited renewal of the midgut epithelium is sufficient to avoid premature death, but ISC/EB ablation can sensitize the animals to chemically induced damage.…”
Section: Resultsmentioning
confidence: 99%
“…S3, D–F). We previously reported that flies lacking ISCs did not demonstrate decreased survival under control conditions; however, these flies had decreased rates of survival in response to bleomycin exposure ( Resende et al, 2017 ). Collectively, these data indicate that limited renewal of the midgut epithelium is sufficient to avoid premature death, but ISC/EB ablation can sensitize the animals to chemically induced damage.…”
Section: Resultsmentioning
confidence: 99%
“…Stem cells in Drosophila melanogaster are a versatile system with which to study age related changes in regenerative potential ( Lucchetta and Ohlstein, 2017 ; Fabian and Brill 2012 ; Resende et al, 2017 ; Resnik-Docampo et al, 2017 ). Defects in GSC function in aged flies have been identified and are in line with hypothesized defects in aging human stem cells: decreased proliferative capacity, accumulation of DNA damage, and eventual loss of stem cells ( Zhao et al, 2008 ; Kao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila ISCs undergo cell division to renew themselves and generate uncommitted enteroblasts (EBs), which are progenitor cells that can further differentiate into either secretory enteroendocrine cells (EEs) or absorptive enterocytes (ECs) [ 44 ]. ISCs and EBs are characterized by the expression of the snail family transcription factor escargot ( esg ) [ 42 ] and headcase ( hdc ) [ 45 ]. Drosophila ISCs do not reside within discrete anatomical locations equivalent to the mammalian crypts and are instead scattered along the basal membrane of the intestinal epithelium.…”
Section: The Adult Drosophila Intestinementioning
confidence: 99%
“…Functional studies of ISCs in the adult Drosophila midgut are less complex. The discovery of esg [ 42 ] and, more recently, hdc [ 45 ] as markers of all stem/progenitor cells (ISCs/EBs), has allowed global targeting of this cell population and unambiguous assessment of their role in intestinal homeostasis and regeneration [ 45 , 79 ]. De-differentiation of committed lineages has not been reported in the adult Drosophila midgut, suggesting a lower degree of plasticity or reserve stem cell potential in the invertebrate tissue when compared to the mammalian intestine.…”
Section: Wnt Signalling In Intestinal Homeostasis and Regenerationmentioning
confidence: 99%